Podejście genderowe w analizie kapitału społecznego = Gender approach in the analysis of social capital - Dzwonkowska-Godula, Krystyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author is interested in the importance of gender in respect of the value of social capital of women and men. In this article the social capital of women and men has been compared on the basis of results of research representative of both Polish society and the Łodź area. Various ways of defining femininity and masculinity, as well as different social roles of women and men, and unequal gender status have been taken into account.
Keywords: gender; social capital; social networks; trust; płeć; kapitał społeczny; sieć społeczna; zaufanie